Biochar-supported nZVI for the removal of Cr(VI) from soil and water: Advances in experimental research and engineering applications. (15th August 2022) - Sun, Peng; Wang, Zhiqiang; An, Shengwei; Zhao, Jian; Yan, Yichen; Zhang, Daijie; Wu, Zhineng; Shen, Boxiong; Lyu, Honghong
Abstract: Over the past decade, biochar-supported nZVI composites (nZVI/biochar) have been developed and applied to treat various pollutants due to their excellent physical and chemical properties, especially in the field of chromium (VI) removal. This paper reviewed the factors influencing the preparation and experiments of nZVI/biochar composites, optimization methods, column experimental studies and the mechanism of Cr(VI) removal. The results showed that the difference in raw materials and preparation temperature led to the difference in functional groups and electron transfer capabilities of nZVI/biochar materials. In the experimental process, pH and test temperature can affect the surface chemical properties of materials and involve the electron transfer efficiency. Elemental doping and microbial coupling can effectively improve the performance of nZVI/biochar composites. In conclusion, biochar can stabilize nZVI and enhance electron transfer in nZVI/biochar materials, enabling the composite materials to remove Cr(VI) efficiently. The study of column experiments provides a theoretical basis for applying nZVI/biochar composites in engineering. Finally, the future work prospects of nZVI/biochar composites for heavy metal removal are introduced, and the main challenges and further research directions are proposed. Graphical abstract: Image 1 Highlights: NZVI/biochar is a highly efficient Cr(VI) removal composite. Pyrolysis temperature and feedstock affect functional groups and electron transfer ability. More efficient and stable effects can be achieved by adding stabilizer and element doping. Flow rate is the key factor affecting removal efficiency in column experiment. Multiple removal mechanisms coexist in nZVI/biochar Cr(VI) removal.